Project management in the development of dynamic capabilities for an open innovation era - Patrício, V.; Lopes da Costa, R.; Pereira, L.; António, N. (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The aim of the research is to explain how Project Management (PM) ensures the accumulation, integration, utilization, and reconfiguration of the capabilities and knowledge acquired in projects in order to build dynamic capabilities (DCs). This study also gives insight into how PM can develop DCs through the identification and implementation of project management opportunities. The result of 22 semi-structured interviews with 22 participants from 9 companies of different industries are detailed and framed within theoretical dimensions of DCs: knowledge accumulation, integration, utilization, reconfiguration, sensing, and seizing. As a result, we present the best practices, techniques, and PM tools that allow leveraging DCs in organizations. This qualitative study contributes to a theoretical and empirical discussion about how PM transforms knowledge acquired in projects into routines and learning practices that allow organizations to develop or reshape capabilities.